The Importance of Food Security at The Family Level in Preventing Stunting in Indonesia: Pentingnya Ketahanan Pangan di Tingkat Keluarga dalam Pencegahan Stunting di Indonesia - Nanik Suhartatik; Fadilah Husnun; Irvia Resti Puyanda (JAKADIMAS (Jurnal Karya Pengabdian Masyarakat), 2024)
Stunting is a condition where a child's height does not match the child's age. Stunting is used as an indicator of a child's growth process that is not good. Stunting is also used as an indicator of the achievements of a country's development process as outlined in the sustainable development goals (SDGs). Mojosongo Village is one of the sub-districts in Banjarsari District, Surakarta, Central Java. One of the sub-districts with still high stunting rates in Surakarta City. Handling of stunting in the City of Surakarta is carried out through several areas including economic, environmental, educational, facilities and infrastructure, and monitoring in the health sector. Based on the identification carried out, it was discovered that factor causing stunting is food availability at the family level or what is usually called food security. To support food security at the family level, one thing parents can do is provide food that is varied, nutritious and affordable for children. Efforts that can be made are by providing a varied menu as a complementary food for breast milk (MP-ASI). Fulfilling nutrition at the family level requires increasing family skills in providing healthy food, so it is necessary to provide training on MP-ASI processing for health cadres or parents. The training was carried out using lecture and direct practice methods and was attended by 46 participants consisting of health cadres in Mojosongo Village, UPPKB, and also parents. There are 4 high-protein processed ingredients provided, namely cheese potato sticks, milk corn pudding, macaroni schotel, and also soa noodles. Training participants, especially health cadres, gain knowledge and skills that are useful for preparing additional food (Pemberian Makanan Tambahan, PMT) for families of stunting sufferers.